Manajemen Pendidikan Islam dalam Era Digital: Strategi Kurikulum Berbasis Nilai Islam untuk Menghadapi Tantangan Globalisasi - Wardhani, Suryaningtiyas Puspa; Bedi, Fisman; Fitri, Tin Amalia (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2024)
Globalization and the digital era have a significant impact on Islamic education, especially in terms of preserving and incorporating Islamic values into the curriculum.  The purpose of this research is to examine how Islamic education faces challenges and opportunities in maintaining core values amidst globalization.  Data were collected using a descriptive qualitative method through literature studies and interviews with Islamic education experts experienced in curriculum development.  Research results show that the Islamic education curriculum must be adjusted if it is to remain relevant and effective in shaping students' character in the modern era.  Utilizing technology to deliver content in a more interactive and engaging way must uphold fundamental principles such as morality, ethics, and spirituality.  So, in order for Islamic education to play its best role in facing the challenges of globalization, the curriculum must be adjusted while maintaining Islamic values.  This research provides educators and policymakers with insights into the importance of developing a curriculum that combines the application of technology and the preservation of Islamic values.